The use of YouTube as Learning Media in English class - Asmaulhusna; Nurdin Noni; Kisman Salija (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2024)
In this era, technology has also developed into the world of education. This can be an opportunity for teachers to combine English language learning by using technology as a medium. One of the technological developments in learning is using social media such as YouTube. This research was conducted to 1) determine the use of YouTube as an English learning medium. 2) find out students' perceptions after using YouTube as a learning medium. 3) determine students' learning interest in using YouTube as an English learning medium. The research method used is qualitative with a descriptive approach. The research results show that 1) The majority of students gave positive perception toward the use of YouTube as learning media in English class YouTube has Interesting visual and clear explanation, helps student to understand the material easily, Easy to access and repeatable, it can be Additional learning resources, provided additional features for Language Learners, it can create interesting and entertaining learning and also it can increase student concentration. 2) The implementation of YouTube in learning is carried out in three stages: a) preparation, the teacher prepares a lesson plan, prepares the YouTube video that related to the material, also prepares facilities and infrastructure that support learning; b) implementation, the teacher shows a video to convey the material, and provides a brief explanation; and c) evaluation, the teacher provides exercises to ensure the material is well received. Furthermore, 3) the majority of students are happier, more active, more enthusiastic and can focus in learning English using YouTube as learning media. So, it can be said that students' interest in learning English by using YouTube as a learning medium quite good.